The Role of Knowledge Brokers in Facilitating Knowledge Transfer within and between Organizations - Khalif, Ahmed (European Journal of Information and Knowledge Management, 2024)
Purpose: The general objective of the study was to investigate the role of knowledge brokers in facilitating knowledge transfer within and between organizations. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the role of knowledge brokers in facilitating knowledge transfer within and between organizations. Preliminary empirical review revealed that knowledge brokers played a crucial role in facilitating knowledge transfer within and between organizations by acting as intermediaries between knowledge creators and users. They effectively bridged gaps, built networks of trust, translated complex information into accessible formats, and provided tailored support to various stakeholders. Their efforts enhanced the accessibility, relevance, and application of knowledge, fostering a culture of continuous learning and innovation. Additionally, knowledge brokers contributed to the broader diffusion of innovations and best practices, promoting systemic improvements and a more interconnected knowledge ecosystem. Unique Contribution to Theory, Practice and Policy: The study recommended enhancing theoretical frameworks to explicitly include knowledge brokers, formally recognizing and supporting their roles within organizations through training and development, and creating policies that incentivize their integration into public and private sectors. It also suggested developing interdisciplinary networks for collaboration, implementing robust evaluation mechanisms to assess the impact of knowledge brokers, and ensuring long-term sustainability through ongoing funding and institutional support. These measures aimed to optimize the impact of knowledge brokers in driving innovation, improving performance, and facilitating effective knowledge transfer within and between organizations.